Genetic, breeding and phytopathological study of winter wheat cultivars resistance to yellow rust P.striiformis West.f.sp.tritici (Experimental biology, 2015)
Yellow rust is harmful wheat disease causing severe economic damage. Based on the results of the field evaluation identified four wheat varieties resistant to yellow rust (перечислить сорта) were identified. 6 wheat cultivars showed exceeding in most of productivity traits. According to phytopathological analysis and agronomic traits evaluation four cultivars of winter wheat were selected.
Keywords: wheat; grade; yellow rust; genetics of resistance